Influence of the airflow in a solar passive building on the indoor air quality and thermal comfort levels - Conceição, Eusébio (2020)
The influence of the airflow in a solar passive building on the indoor air quality and thermal comfort levels was investigated. The numerical study for a university library was conducted using a software that simulates the building thermal behavior with complex topology, in transient conditions, for evaluating the indoor air quality and occupants' thermal comfort levels for typical summer and winter days. Solar radiation was used as a renewable energy source to increase simultaneously the thermal comfort and air quality levels and reduce building energy consumption. Regarding the solar passive building, consideration was given to all of the building structure envelope, shading devices and interior details, while in the solar active building active ventilation was used. To analyze the airflow that simultaneously provides the best indoor air quality and thermal comfort levels, a new integral methodology based on the minimization of the total number of uncomfortable hours was used. The results show that it was possible to determine an air change rate that ensures a good compromise between thermal comfort and indoor air quality. An optimal air change rate of two and three renewals per hour had been determined, respectively, for winter and summer conditions.